2008
DOI: 10.1016/j.cis.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Analytical phase diagrams for colloids and non-adsorbing polymer

Abstract: We review the free-volume theory (FVT) of Lekkerkerker et al. [Europhys. Lett. 20 (1992) 559] for the phase behavior of colloids in the presence of non-adsorbing polymer and we extend this theory in several aspects:(i) We take the solvent into account as a separate component and show that the natural thermodynamic parameter for the polymer properties is the insertion work Πv, where Π is the osmotic pressure of the (external) polymer solution and v the volume of a colloid particle. (ii) Curvature effects are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
204
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(216 citation statements)
references
References 91 publications
12
204
0
Order By: Relevance
“…In the "protein" limit, q r > 1, such approaches begin to fail as the overall free energy of the system becomes sensitive to details of the polymer. A previous study of the phase behavior of lattice colloids and linear chains demonstrated * azp@princeton.edu that proposed rescaling arguments involving the polymer correlation length, ξ, qualitatively failed to collapse the colloid-rich portion of the binodal in the protein limit [16]; this observation had not been previously captured in simulation or analytical models which suggested such a collapse should be possible [17][18][19], however it is consistent with recent experimental findings [20].…”
supporting
confidence: 67%
“…In the "protein" limit, q r > 1, such approaches begin to fail as the overall free energy of the system becomes sensitive to details of the polymer. A previous study of the phase behavior of lattice colloids and linear chains demonstrated * azp@princeton.edu that proposed rescaling arguments involving the polymer correlation length, ξ, qualitatively failed to collapse the colloid-rich portion of the binodal in the protein limit [16]; this observation had not been previously captured in simulation or analytical models which suggested such a collapse should be possible [17][18][19], however it is consistent with recent experimental findings [20].…”
supporting
confidence: 67%
“…In particular, we focus on colloidal dispersions comprising large particles, colloids, usually modeled as hard spheres, and polymers in an implicit solvent. These systems are particularly interesting as they show a complex phase diagram which depends crucially on the polymer-to-colloid size ratio: for small ratios, only fluid-solid coexistence is observed, while for larger values an additional fluid-fluid transition is present [79][80][81][82][83][84]. Even in the absence of an explicit solvent, the computation of the full phase diagram is quite difficult, especially if one is interested in polymers with a large degree of polymerization.…”
Section: Single-site Coarse-grained Model For Multicomponent Systemsmentioning
confidence: 99%
“…This value still exceeds the theoretical threshold below which the liquid phase is expected to be metastable, and corresponds to a depletion thickness to colloid radius ratio of q s ∼ 0.3-0.4. The phase diagram for a system with this value of q s may be expected to correspond roughly to that provided in figure 1.1 of reference [34], which features 'gas-liquid', 'gas-solid' and 'fluid-solid' phase boundaries. It is noticeable that the solid phase is characterised by η c 0.54, corresponding to the well-known coexistence packing fraction for pure HS, and significantly in excess of the total packing fraction (polymers + colloids) of the denser of the two phases we find in our simulations.…”
Section: Studies Of the Separate Polymer-rich And Colloid-rich Phasesmentioning
confidence: 91%
“…To date, the phase behaviour of colloid-polymer mixtures has been addressed in a number of theoretical studies, in addition to those already mentioned; see, for example, references [34,43,[47][48][49][50][51][52][53][54][55][56][57]. Among these, we highlight the studies [43,[53][54][55]58] based on Wertheim's first-order thermodynamic perturbation theory (TPT1) [59,60]; these deal with the polymer at the monomer segment level [61], in contrast to studies based on the AO model or the AO approximation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation